Simulation Research for the Influence of Mining Sequence on Coal Pillar Stability under Highwall Mining Method - Jing Huang; Fanbao Meng; Ge Wang; Yingkui Wu; Jinhao Wen (Geofluids)
Highwall mining, which is referred to the technique of extracting coal from the bottom of an exposed highwall, features safety, efficiency, and economy. According to existing highwall mining methods, the mining sequence has a great influence on highwall stability. Based on a highwall mining project in Australia, this study adopted the FLAC3D numerical simulation method to investigate the stability of coal pillars with different mining sequences. The results show that different mining sequences of boreholes exert a great effect on highwall stability. Compared with sequential mining, the skip mining method achieves higher speed of highwall stabilization and smaller plastic zone of coal pillar with its maximum strength decreasing by 12%. By adjusting the mining sequence scientifically, the coal pillar failure and roof collapse caused by the deviation of mining angle can be avoided. The results may provide a new angle for the studies on the coal pillar layout and stability design in highwall mining.